A escrita e a criança com síndrome de Down: uma relação possível na escola regular - Silva, Maria Karolina de Macedo (2010)
The school inclusion is based on respect for diversity and the belief that everyone has the capacity to learn and develop, for this the school needs to prepare itself to meet the differences and provide a meaningful learning for everyone, including those with Down syndrome. It is in the interaction with others that children develop their skills and exchange substantial experiences to learn the school and non school knowledge. Among the knowledge the school must offer students, there is one that is indispensable to the present society; the writing, because writing is a way to Interact, to communicate and to build autonomy to relate in society. Before exposed, the research that started this study aimed to investigate the level of the writing conceptualization of children with Down syndrome during the literacy process in a regular school of the private school network in the city of Natal/RN. For carrying out this study, initially we conducted a qualitative research, using the bibliographical as a methodological recourse, seeking to the deepening of information, based on the literature about the subject, which allowed us to collect data about people with Down syndrome, their education and the process of the writing acquisition. Later, a case study was performed, involving free observation in the room and interviews with teachers and children, trying to verify how this writing acquisition process occurs by children with Down syndrome. The data analyzed and information recorded demonstrated that the school inclusion, when taken seriously, benefits the learning of writing for children who have intellectual deficit, and, mainly, they develop in this environment and are able to learn to write, as long as their own pace are respected